Survey and Planning in Soil Conservation - Mansingh, Bisan (Journal of Soil and Water Conservation, 2022)
Soil Conservation in the true and real sense is proper soil and water manage- ment for systematic increase in produc- tion at the highest level. It is not merely terracing, contouring, strip-cropping, filling, gullies, or planting excessively steep and erod- able land with grass and trees; it is that and whatever else needs to be done to keep the soil permanently productive or make it more productive. It means drainage if the land is too wet and irrigation if it is too dry; it means addition of fertilizers and organic matter if the soil is deficient in these cons- tituents. According to the experiments carried out in Bombay State it can safely be concluded that in India more than one lac acres of good land has been going out of cultivation every year and a much larger area has been steadily losing its productive capacity due to the ravages of water and wind erosion. Besides this loss of soil another distressing feature is that this precious top soil is carried to the rivers and where there are river-valley projects the reservoirs are being silted up. Otl the whole the position is simply alarming. Now the question arises how this loss of soil and sub-soil water and the silting up of the. reservoirs of the river-valley projects can be prevented and what will be the agency to accomplish this gigantic task. There are possibilities of achieving this objective if it is clearly realized by both the government and the people that national action may be led and aided by the govern- ment, but the soil must be conserved ulti- mately by those who till the land and live by its products. \Vithout a wide-spread recognition of this responsibility any govern- mental action must be doomed to eventual futility and failure.